Post-abortion contraception: how to make the right choice? - Yuliya E. Dobrokhotova; Metanat R. Narimanova; Svetlana A. Khlynova; Liudmila V. Saprykina; Irina Iu. Il'ina (IP Berlin A.V., 2021)
More than 600 thousands abortions are performed annually in Russia. Women presenting for abortion care are often motivated by the pregnancy to use effective contraception; they are also at high risk for repeat unintended pregnancy. Contraceptive counseling and the supply of contraceptive methods are part of post-abortion care and positively influence the subsequent use of contraceptive methods. Oral contraceptives (OCs) following induced abortion offer a reliable method to avoid repeated abortion. Immediate administration of combined OCs after abortion may reduce vaginal bleeding time and amount, shorten the menstruation recovery period, and reduce the risk of complications and unintended pregnancies. Сombination of ethinylestradiol 30 g + drospirenone 3 mg demonstrates the advantages of a low estrogen dose with the antimineralocorticoid activity of drospirenone that is responsible for the drugs significant antiandrogenic and antimineralocorticoid effects, reflected clinically in lower rates of adverse events including less fluid retention. Сombination of ethinylestradiol 30 g + drospirenone 3 mg and Metafolin has similar contraceptive efficacy, side effect, safety and benefits profile to other drospirenone-containing contraceptives. The article presents the results of the latest studies about using of combined OCs (ethinylestradiol 30 g + drosperinone 3 mg and Metafolin) after abortion.